Dual Specificity Phosphatases: From Molecular Mechanisms to Biological Function - Pulido, Rafael; Lang, Roland (International Journal of Molecular Sciences, 2019)
Dual specificity phosphatases (DUSPs) constitute a heterogeneous group of enzymes, relevant in human disease, which belong to the class I Cys-based group of protein tyrosine phosphatase (PTP) gene superfamily [...].
CRIS-Team Scopus Importer:2019-09-20